2017
DOI: 10.1038/s41598-017-05348-3
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pain control by blocking oxidized phospholipid-mediated TRP channel activation

Abstract: Phospholipids occurring in cell membranes and lipoproteins are converted into oxidized phospholipids (OxPL) by oxidative stress promoting atherosclerotic plaque formation. Here, OxPL were characterized as novel targets in acute and chronic inflammatory pain. Oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphocholine (OxPAPC) and its derivatives were identified in inflamed tissue by mass spectrometry and binding assays. They elicited calcium influx, hyperalgesia and induced pro-nociceptive peptide release.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 86 publications
7
89
0
Order By: Relevance
“…Phosphocholine (PC) containing oxidized phospholipids (OxPL) are a prominent example, and the PC headgroup of OxPL in OxLDL (as a lipid or OxPL-protein adduct) is recognized by macrophage scavenger receptors and TLRs, by innate protein CRP and by the IgM natural antibody (NAb) E06 1 . OxPLs accumulate in OxLDL, apoptotic cells and microparticles released by activated and dying cells 4,6 and are ubiquitous in a wide variety of inflammatory settings, including atherosclerosis 7 , pulmonary 8,9 and neurological diseases 10-12 and NASH 13 among others 1 . In addition, OxPL present on Lp(a) are thought to mediate, in part, the ability of Lp(a) to promote atherogenesis and calcific aortic valve disease (CAVD) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Phosphocholine (PC) containing oxidized phospholipids (OxPL) are a prominent example, and the PC headgroup of OxPL in OxLDL (as a lipid or OxPL-protein adduct) is recognized by macrophage scavenger receptors and TLRs, by innate protein CRP and by the IgM natural antibody (NAb) E06 1 . OxPLs accumulate in OxLDL, apoptotic cells and microparticles released by activated and dying cells 4,6 and are ubiquitous in a wide variety of inflammatory settings, including atherosclerosis 7 , pulmonary 8,9 and neurological diseases 10-12 and NASH 13 among others 1 . In addition, OxPL present on Lp(a) are thought to mediate, in part, the ability of Lp(a) to promote atherogenesis and calcific aortic valve disease (CAVD) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others have shown that OxPL including oxidized 1‐palmitoyl‐2‐arachidonoyl‐sn‐glycero‐3‐phosphocholine (OxPAPC) activate heterologous and native TRPA1 as well as TRPV1 channels in vitro . Once locally injected, these lipids elicit thermal and mechanical hypersensitivity as well as acute nociception in vivo (Patwardhan et al ., ; Liu et al ., ; Oehler et al ., ). Furthermore, we showed that OxPAPC‐mediated activation of TRPA1 channels in vitro , as well as thermal and mechanical hypersensitivity induced by OxPAPC in vivo are blocked by a function‐blocking autoantibody against oxidized phosphatidylcholine (OxPC), the E06 monoclonal antibody (Oehler et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Once locally injected, these lipids elicit thermal and mechanical hypersensitivity as well as acute nociception in vivo (Patwardhan et al ., ; Liu et al ., ; Oehler et al ., ). Furthermore, we showed that OxPAPC‐mediated activation of TRPA1 channels in vitro , as well as thermal and mechanical hypersensitivity induced by OxPAPC in vivo are blocked by a function‐blocking autoantibody against oxidized phosphatidylcholine (OxPC), the E06 monoclonal antibody (Oehler et al ., ). In addition, mechanical hypersensitivity in hind paw inflammation induced by complete Freund's adjuvant (CFA) and in collagen‐induced arthritis was ameliorated.…”
Section: Introductionmentioning
confidence: 97%
“…Channels of the Transient Receptor Superfamily (TRP), such as TRPV1, TRPM8, and TRPA1, are non-selective cation channels that conduct calcium and sodium into a range of cell types in mammals. They are present on sensory neurons, and were initially identified as having a role in nocioception because of their responsiveness at the molecular level to plant secondary metabolites that are nocimimetic (e.g., Capsaicin) and to compounds that are otherwise pungent and mimic burning or cooling sensations (e.g., allicin, cinnamaldehyde, menthol) [31][32][33][34][35][36]. Several of these channels are targets for cannabinoids including THC, CBD and CBN and some minor Cannabis compounds [37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%